Positioning the six‐month review in the recovery process post‐stroke: The ideology of personal responsibility. (30th October 2018) - Abrahamson, Vanessa; Wilson, Patricia
Abstract: Stroke is the UK's fourth highest cause of death and an estimated 300, 000 people in England are living with related disability. This paper explores the six‐month review (6MR), a policy initiative that aimed to ameliorate unmet need. A multiple case study approach underpinned by critical realism was used to elicit the views of patients, carers, providers and commissioners across three sites using interviews, observations and documentation. Forty‐six patients (age range 28–91 years), 30 carers and 28 professionals were interviewed between December 2015 and October 2016. Twenty‐nine reviews were observed. Data was analysed thematically across sites. 6MRs carried out by stroke nurse specialists (SNSs) were found to be more medically orientated than those completed by a Stroke Association (SA) co‐ordinator who focused on social issues. Reviewers regarded reviews primarily as an opportunity to address unmet need and signpost to further services. Patients responded in three different ways: proactive and engaged, reflected an active orientation to recovery and self‐management; proactive and self‐managing on their own terms, encompassed patients who were striving for independence but took their own approach sometimes at odds with that of clinicians; and passive orientation, whereby patients did not engage in rehabilitation or self‐management. Patients identified different priorities to those of reviewers, particularly those with other long‐term conditions and this appeared to contribute to the dissatisfaction that some expressed. In conclusion, there was little evidence that the 6MR played a key role in recovery. Locally defined outcomes for the 6MR reflecting national policy were not substantiated by the findings. Our findings suggest that the 6MR should review therapy goals and facilitate patient‐led goals. Reviewers should be allowed the freedom to individualise the process rather than adhering to a rigid framework dictated by national policy and local protocols.